2018
DOI: 10.1111/ibi.12586
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and processes in shorebird survival rates: a global review

Abstract: PortugalChanges in demographic rates underpin changes in population size, and understanding demographic rates can greatly aid the design and development of strategies to maintain populations in the face of environmental changes. However, acquiring estimates of demographic parameters at relevant spatial scales is difficult. Measures of annual survival rates can be particularly challenging to obtain because large-scale, long-term tracking of individuals is difficult and the resulting data contain many inherent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 65 publications
(120 reference statements)
5
48
0
Order By: Relevance
“…Four CJS models had AICc values <2, including the simplest model ( AICc = 0.64), which estimated p at 0.52 (CI = 0.31-0.71) and ϕ at 0.32 (CI = 0.23-0.43). An apparent survival rate of 0.32 is notably low for a wader species (Méndez et al, 2018) but is within the range of 0.17 to 0.56 reported from sites in Alaska (Colwell et al, 1988;Schamel and Tracy, 1991;Sandercock, 1997) and likely reflects a low site fidelity rather than survival. Nevertheless, a weak effect of geolocator deployment cannot be ruled out, considering we could not compare against a control group without a geolocator, and knowing that a geolocator attached to a leg flag and weighing >2.5% of the body mass led to lower return rates in other small wader species (Weiser et al, 2016).…”
Section: Introductionsupporting
confidence: 71%
“…Four CJS models had AICc values <2, including the simplest model ( AICc = 0.64), which estimated p at 0.52 (CI = 0.31-0.71) and ϕ at 0.32 (CI = 0.23-0.43). An apparent survival rate of 0.32 is notably low for a wader species (Méndez et al, 2018) but is within the range of 0.17 to 0.56 reported from sites in Alaska (Colwell et al, 1988;Schamel and Tracy, 1991;Sandercock, 1997) and likely reflects a low site fidelity rather than survival. Nevertheless, a weak effect of geolocator deployment cannot be ruled out, considering we could not compare against a control group without a geolocator, and knowing that a geolocator attached to a leg flag and weighing >2.5% of the body mass led to lower return rates in other small wader species (Weiser et al, 2016).…”
Section: Introductionsupporting
confidence: 71%
“…Informed priors may also originate from comparative studies, such as reviews of vital rates in closely related taxa (e.g., global reviews of survival rates in shorebirds; Méndez et al. ) or larger‐scale studies that use allometric scaling (e.g., survival vs. body mass relationships in birds and mammals; McCarthy et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Wetlands, which account for some of the main breeding and non-breeding habitats of shorebirds, are disappearing at an alarming rate globally, and by working in the field on a day-to-day basis, we saw numerous examples of nest predation by feral cats and dogs, illegal hunting and rapid habitat loss. True, many shorebirds have flexible breeding strategies-indeed, the fluctuating nature of suitable habitats is one of the theories put forward to explain diverse breeding strategies (Oring 1986;Erckmann 1981)-nonetheless, if suitable habitats decline, this can only mean declining overall population sizes, reduced productivity and/or increased mortality (Méndez et al 2018). Shorebird species have indeed gone extinct since records began (e.g.…”
Section: Biodiversity Conservationmentioning
confidence: 99%
“…More recently, Kubelka et al (2018) has shown that rates of nest predation of many shorebirds have increased substantially in recent years, and that the largest increase was in the Arctic. The effects on Arctic shorebirds, many of which are long-distance migrants, are twofold: nest mortality is increasing, and adult survival is decreasing (Méndez et al 2018). These pressures are, unfortunately, likely to feed into declining shorebird populations worldwide, and especially in the Arctic (Kubelka et al 2018).…”
Section: Biodiversity Conservationmentioning
confidence: 99%